GE_GERICHTE P/9148/2013 vom 30. Oktober 2015 - GE Cour de justice (2015)
VOL(DROIT PÉNAL); INFRACTION PAR MÉTIER; PRÉSOMPTION D'INNOCENCE; CONFISCATION(DROIT PÉNAL) | CP.139.2; CP.139.1; CP.144; CP.186; LCR.94.1.a